Media Advocacy for Immunization: Understanding Journalistic Awareness and Its Effects on Public Health in India - Padmini Jain (Journal of Advanced Research in Journalism & Mass Communication, 2019)
This study aims to evaluate the awareness and understanding among media personnel regarding the Routine Immunization Program (RIP) in India. It investigates their knowledge of the program’s details, its importance, and the impact of their reports on the public’s perception of immunization. Utilizing a structured questionnaire distributed to media professionals, the study assesses various aspects of their awareness and understanding of RIP. Key findings reveal that while 63% of media personnel recognize the importance of immunization in reducing child mortality, only 20% accurately understand the specifics of vaccine-preventable diseases covered by RIP. Furthermore, 90% acknowledge the potential negative impact of inaccurate reporting on immunization programs. Despite a general awareness of RIP’s significance, there is a notable deficiency in detailed knowledge and understanding of the program’s processes among media personnel. The implications of these findings underscore the need for enhanced training and education for media personnel on health reporting. Improved media coverage and accurate reporting on immunization can significantly influence public perception and participation in health programs, thereby supporting better health outcomes in India. This study highlights the critical role of media in public health advocacy and the importance of informed and responsible journalism in promoting effective health interventions.